The rising moon political change in Sarawak 1959-1972 - Leigh, Michael B. (Strategic Information and Research Development Centre, 2018)
The Rising Moon was the first in-depth study of the beginnings of modern politics in Sarawak between 1959 and 1972. The plural society of that state offered a stark contrast to that elsewhere in Malaysia, for in Sarawak viable political parties spanned ethnic divisions, a development that had not then taken place in the other parts of the nation. Side-by-side with the development of politics came the integration of Sarawak within Malaysia, and all the attendant tensions that followed from the merging of this its largest state within an expanded federation. The resultant pattern of politics was dynamic, and throughout this phase remained quite tentative due in large part to Indonesian confrontation and the armed activities of the local communist organisation. Amongst the states of Malaysia, Sarawak is unique, as all groups are in a minority, whether they be defined by ethnicity, religion or mother tongue. That necessitated political compromise spanning ethnic, religious and cultural divisions.